2019
DOI: 10.1097/tp.0000000000003038
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Donor Glomerulopathy Is a Possible Cause of Abnormal Urinalysis in Adults Receiving Small Pediatric Donor Kidneys

Abstract: Background. Reports about prognosis of adults receiving small pediatric-donor kidneys (PDK) as compared to those receiving elder pediatric or adult donor kidneys (ADKs) are controversial. This study aimed to examine the outcomes of adults receiving small PDK and possible prognostic factors. Methods. The records of adults who received kidneys from donors < 10 years old at our center from July 1, 2011 to June 30, 2018 were reviewed. Results. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Donor−recipient size mismatch is controversially discussed regarding its predictive value for graft function in children and adults. Cardiovascular complications, abdominal compartment [14], or downregulation of filtration without the ability to adapt function later in case of large‐for‐size organs contrast concerns regarding hyperfiltration injury or graft thrombosis reported for small donor‐size [6,10,24]. Although a significant proportion of patients in our study had a mismatch of D/R (<0.75/>1.25), multivariate analysis revealed no significant impact of this parameter on graft survival.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Donor−recipient size mismatch is controversially discussed regarding its predictive value for graft function in children and adults. Cardiovascular complications, abdominal compartment [14], or downregulation of filtration without the ability to adapt function later in case of large‐for‐size organs contrast concerns regarding hyperfiltration injury or graft thrombosis reported for small donor‐size [6,10,24]. Although a significant proportion of patients in our study had a mismatch of D/R (<0.75/>1.25), multivariate analysis revealed no significant impact of this parameter on graft survival.…”
Section: Discussionmentioning
confidence: 51%
“…Jiang et al . [10] reported adult SDK‐recipients presenting with proteinuria and Alport‐like splitting and lamination of the glomerular basement membrane (GBM). Histological findings were detected within 4–18 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of "size mismatch glomerulopathy (SMG)" which affects <10% of adult recipients, is defined by the process of hyperfiltration injury and adaptation secondary to higher recipient blood pressure and blood flow within the glomeruli in pediatric donor allografts of <3 years of age [18]. Since the glomerular size in the pediatric donors is smaller and often immature, DOI: 10.1159/000517124 with extremely thin glomerular capillary basement membranes, exposure to the direct mechanical adultlevel hemodynamic forces appears to stress and injure the glomerular epithelial cells, resulting in this unique lesion [19].…”
Section: Definition and Backgroundmentioning
confidence: 99%
“…At 5 years posttransplantation, there is >50% graft survival. A recent study showed that a higher donor age, donor weight, or donor kidney volume may be protective and may not tend to develop SMG in the recipient [ 18 , 19 ].…”
Section: Size Mismatch (Pediatric Donor Related) Glomerulopathy Secon...mentioning
confidence: 99%